2022
DOI: 10.1007/s00018-022-04190-9
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of epithelial sodium channel (ENaC) activity in cystic fibrosis cells by epigenetic targeting

Abstract: The pathogenic mechanism of cystic fibrosis (CF) includes the functional interaction of the cystic fibrosis transmembrane conductance regulator (CFTR) protein with the epithelial sodium channel (ENaC). The reduction of ENaC activity may constitute a therapeutic option for CF. This hypothesis was evaluated using drugs that target the protease-dependent activation of the ENaC channel and the transcriptional activity of its coding genes. To this aim we used: camostat, a protease inhibitor; S-adenosyl methionine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 81 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…Studies have suggested that imbalanced ion transport via CF epithelia may be mitigated by inhibiting ENaC. 80,81 Therefore, a reduction in ENaC activity may be an alternative approach for treating CF. Recently, a study suggested that the activity of ENaC may be downregulated by epigenetic modulation, which acts on both DNA methylation and chromatin condensation, as well as inhibition of extracellular peptidases.…”
Section: Curcuminmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have suggested that imbalanced ion transport via CF epithelia may be mitigated by inhibiting ENaC. 80,81 Therefore, a reduction in ENaC activity may be an alternative approach for treating CF. Recently, a study suggested that the activity of ENaC may be downregulated by epigenetic modulation, which acts on both DNA methylation and chromatin condensation, as well as inhibition of extracellular peptidases.…”
Section: Curcuminmentioning
confidence: 99%
“…Recently, a study suggested that the activity of ENaC may be downregulated by epigenetic modulation, which acts on both DNA methylation and chromatin condensation, as well as inhibition of extracellular peptidases. 81 In addition, previous research has suggested that curcumin may have an effect on CF airway cells, which it may inhibit expression of the ENaC gene. 81 Lastly, it should be noted that oxidative stress plays a crucial role in the pathogenesis of cystic fibrosis.…”
Section: Curcuminmentioning
confidence: 99%
See 2 more Smart Citations
“…CFTR has also been proposed to inhibit ENaC activity through direct physical interactions, and dehydration of CF ASL is driven by ENaC ( Stutts et al, 1995 ). Thus, stimulation of alternative chloride channels ( Xu et al, 2005 ; Liu et al, 2015 ; Quesada and Dutzler, 2020 ) or inhibition of sodium absorption ( Blacona et al, 2022 ) may be able to compensate for the lack of CFTR-mediate Cl − secretion in CF airways or to maximize the efficacy of gene therapies aiming at CFTR . Notably, it was reported that proteasome modulation agent doxorubicin facilitated long-term functional inhibition of ENaC currents.…”
Section: Challengesmentioning
confidence: 99%